2020
DOI: 10.1007/s10661-019-8049-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic modelling of a flood-prone tidal river using the 1D model MIKE HYDRO River: calibration and sensitivity analysis

Abstract: Hydrodynamic modeling is a powerful tool to gain understanding of river conditions. However, as widely known, models vary in terms of how they respond to changes and uncertainty in their input parameters. A hydrodynamic river model (MIKE HYDRO River) was developed and calibrated for a flood-prone tidal river located in South East Queensland, Australia. The model was calibrated using Manning's roughness coefficient for the normal dry and flood periods. The model performance was assessed by comparing observed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The river width at K. Agraharam was divided in 100 m intervals 2). A similar kind of trend has been observed in previous studies (Tehrani et al, 2020;Timbadiya et al, 2014;. The underestimation of peak values can be due to negligence of the confluence of the Krishna River with the Tungabhadra River.…”
Section: Calibration Of the Model Using Dem Derived Cross-sections Of 30 M And 90 M Resolutionssupporting
confidence: 88%
“…The river width at K. Agraharam was divided in 100 m intervals 2). A similar kind of trend has been observed in previous studies (Tehrani et al, 2020;Timbadiya et al, 2014;. The underestimation of peak values can be due to negligence of the confluence of the Krishna River with the Tungabhadra River.…”
Section: Calibration Of the Model Using Dem Derived Cross-sections Of 30 M And 90 M Resolutionssupporting
confidence: 88%
“…The model structure and boundary conditions can be used to explain this spatial difference. Some studies indicated that boundary conditions strongly impact the measured data of gauging stations close to the boundary conditions (Dung et al, 2010;Jahandideh-Tehrani et al, 2020;Yang et al, 2014). The weakest sensitivity region can be found in the north of the study area close to the water boundary.…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…Detailed measurement data can be used to identify the distribution of n-values by hydrodynamic model calibration (Orlandini, 2002). In practice, global (Parhi et al, 2012;Timbadiya et al, 2011) and spatially varying n values (Attari & Hosseini, 2019;Jahandideh-Tehrani et al, 2020;Ong et al, 2017) are commonly used in model calibration. It is simple and effective to take a global roughness value for a few rivers having similar cross-sections without floodplains under the condition of limited water level change.…”
Section: Introductionmentioning
confidence: 99%
“…Natural hazards refer to the frequency and intensity of hazards, and vulnerability denotes the susceptibility of the exposed elements to hazards, while exposure indicates population or assets located in flood-prone areas [11,14]. Many effective approaches have been used in FIR, such as expertise-based methods like analytic hierarchy process [15][16][17][18], probability-based evaluations like Bayesian networks [13,19], machine-learning-based approaches like neural networks [20][21][22][23][24], and hydrological and hydraulic models [25][26][27].…”
Section: Introductionmentioning
confidence: 99%